Reviews. Issue 1 (1st May 2015) - Brooking, Tom; Biskup, Przemyslaw; Bracefield, Hilary; David-Ives, Corinne; Carter, Lynette; Russell, Khyla; Tabe, Tammy; Sofo, Giuseppe; Aitken, Tom; Biskup, Przemyslaw; Tokolyova, Tatiana; Meaher, Augustine; et al.
Encounters: The Creation of New Zealand. A History, Paul Moon (2013) Auckland: Penguin New Zealand, 432 pp., ISBN 978 0 1435 6850 6 (hbk), NZ$55Changing Times: New Zealand since 1945, Jenny Carlyon and Diane Morrow (2013) Auckland: Auckland University Press, 520 pp., ISBN 978 1 8694 0782 7 (pbk), NZ$49.99Webs of Empire: Locating New Zealand's Colonial Past, Tony Ballantyne (2012) Wellington: Bridget Williams Books, 374 pp., ISBN 978 1 9271 3143 5 (pbk), NZ$49.99Flying Kiwis: A History of the OE, Jude Wilson (2014) Dunedin: Otago University Press, 296 pp., ISBN 978 1 8775 7826 7 (pbk), NZ$44.99Kerikeri Mission and Kororipo Pa: An Entwined History, Angela Middleton (2013) Dunedin: Otago University Press, 76 pp., ISBN 978 1 8775 7834 2 (pbk), NZ$29.95Ko te whenua te utu / Land is the price: Essays on Maori History, Land and Politics, M. P. K. Sorrenson (2014) Auckland: Auckland University Press, 344 pp., ISBN 978 1 8694 0810 7 (pbk), NZ$49.99The Spirit of Maori Leadership, Selwyn Katene (2013) Wellington: Huia, 180 pp., ISBN 978 1 7755 0121 3 (pbk), NZ$45Greed and Grievance: Ex-militants' Perspectives on the Conflict in Solomon Islands, 1998–2003, Matthew Allen (2013) Honolulu: University of Hawai'i Press, 243 pp., ISBN 978 0 8248 3854 6 (pbk), US$55Mystery Islands: Discovering the Ancient Pacific, Tom Koppel (2012) Suva: University of the South Pacific Press, 345 pp., ISBN 978 9 8201 0888 2 (pbk), US$25Ancient Religions of the Austronesian World: From Australasia to Taiwan, Julian Baldick (2013) London: I.B. Tauris, 256 pp., ISBN 978 1 7807 6366 8 (hbk), £58The Pacific Island in China's Grand Strategy: Small States, Big Games, Jian Yang (2011) Basingstoke: Palgrave Macmillan, 254 pp., ISBN 978 0 2301 1323 7 (hbk), £64No Ordinary Deal: Unmasking the Transpacific Partnership Free Trade Agreement, Jane Kelsey (ed.) (2010) Wellington: Bridget Williams Books, 220 pp., ISBN 978 1 8772 4250 2 (pbk), NZ$39.99Greece, Crete, Stalag, Dachau: A New Zealand Soldier's Encounters with Hitler's Army, Jack Elworthy (2014) Wellington: Awa Press, 256 pp., ISBN 978 1 9272 4912 3 (pbk), NZ$40Transnational Film Culture in New Zealand, Simon Sigley (2013) Bristol: Intellect, 208 pp., ISBN 978 1 8415 0660 9 (pbk), £20Intersecting Identities: Ethnicity, Gender, and Sexuality in Contemporary Fiction from Aotearoa New Zealand, Katharina Luh (2013) Trier, Germany: WVT, 555 pp., ISBN 978 3 8682 1433 8 (pbk), ¤58.50The Lonely and the Alone: The Poetics of Isolation in New Zealand Fiction, Doreen D'Cruz and John C. Ross (2011) Amsterdam: Rodopi, 407 pp., ISBN 978 9 0420 3474 7 (hbk), €102